Chemical Compositions, Sources, and Intra‐Regional Transportation of Submicron Particles Between North China Plain and Twain‐Hu Basin of Central China in Winter. Issue 24 (18th December 2022) - Hu, Yao; Kong, Shaofei; Zheng, Huang; Zheng, Shurui; Yao, Liquan; Cheng, Yi; Niu, Zhenzhen; Chen, Nan; Xu, Ke; Wu, Jian; Liu, Dantong; Zhao, Tianliang; et al.
Abstract: Regional submicron particles (PM1 ) compositions, sources, and interaction are still not clear as the desynchrony in observation. This study focused on PM1 at five sites synchronously in North China Plain and Central China during January 2018. The average PM1 mass concentrations decreased from north to south, with higher values in Luohe (125 ± 59.4 μg m −3 ), followed by borderline cities (54.1–93.3 μg m −3 ) and a south site of Wuhan (63.6 ± 21.5 μg m −3 ). Organic matter (41.8%–51.0%) and secondary inorganic aerosols (SIAs; 28.2%–33.2%) occupied the high fractions for all the five sites. Coal combustion and industrial processes mainly raised the differences in PM1 chemical compositions between regions. The changes of NO3 − /SO4 2− between sites were different as a function of relatively humidity and temperature, reflecting the differences of secondary formation mechanism. For a short intraregional transport case from south to north, PM1 increased from 102 to 185 μg m −3 as the accumulation and aerosol‐planet boundary layer interaction under a stable meteorological condition. For a long‐range transport case from north to south with a high wind speed (5.5 m s −1 ) and boundary layer height (529 m), PM1 decreased by only 0.9 μg m −3 (−1.3%) as the enhanced formation of SIA by 12.6% under increased relative humidity (by 7.2%) and enhanced industrial emission (by 19.1%) at the south site. The results provide a useful data set for modeling PM1 chemical compositions and their impacts and are helpful for regional‐joint control of atmospheric particles and precursor gases. Plain Language Summary: Studies have shown that PM1 has a significant impact on health, climate, and economy, but its chemical compositions, sources, and transport between North China Plain (NCP) and Central China (CC) are still poorly characterized. This study focused on the comprehensive characterization of PM1 species at five sites in NCP and CC during January 2018. The mass concentration of PM1 showed a decreasing trend from north (125 ± 59.4 μg m −3 ) to south (54.1 ± 20.5 μg m −3 ). The organic matter and secondary inorganic aerosols (SIAs) are the two most important species of PM1 which contributed 41.8%–51.0% and 28.2%–33.2%, respectively. Coal combustion and industrial processes mainly raised the differences in chemical compositions between regions. Differences in the transformation of secondary aerosols between the regions indicated the control precursor pollutants should be emphasized. The PM1 increased sharply from 102 to 185 μg m −3 with the influences of vehicle emission (38.6%) when the transport direction was from south to north. The PM1 decreased slightly (−1.3%) as the enhanced formation of SIA (+12.6%) and emission of industry (+19.1%) when the transport direction changed from north to south. The results are helpful for further understanding the differences between regions and regional‐joint control. Key Points: Organic matter and secondary inorganic aerosol are the dominant species in PM1 The chemical species and sources of PM1 varied in North and South China Two transport cases explain the aerosol accumulation and interplay between north and south